The role of historical forcings in simulating the observed Atlantic multidecadal oscillation. Issue 5 (11th March 2017) - Murphy, Lisa N.; Bellomo, Katinka; Cane, Mark; Clement, Amy
Abstract: We analyze the Atlantic multidecadal oscillation (AMO) in the preindustrial (PI) and historical (HIST) simulations from the Coupled Model Intercomparison Project Phase 5 (CMIP5) to assess the drivers of the observed AMO from 1865 to 2005. We draw 141 year samples from the 41 CMIP5 model's PI runs and compare the correlation and variance between the observed AMO and the simulated PI and HIST AMO. The correlation coefficients in 38 forced (HIST) models are above the 90% confidence level and explain up to 56% of the observed variance. The probability that any of the unforced (PI) models do as well is less than 3% in 31 models. Multidecadal variability is larger in 39 CMIP5 HIST simulations and in all HIST members of the Community Earth System Model Large Ensemble than their corresponding PI. We conclude that there is an essential role for external forcing in driving the observed AMO. Key Points: The chance of an unforced PI run correlating as well with the observed AMO as the historical run is less than 3% in 31 out of 41 models The unforced PI models simulate less AMO variance than their forced historical simulations Models need external forcing to explain the magnitude, timing, and multidecadal frequency of the observed twentieth century AMO